Conducting a best evidence systematic review. Part 1: From idea to data coding. BEME Guide No. 13 - Hammick, Marilyn; Dornan, Timothy; Steinert, Yvonne (Medical teacher, 2010)
This paper outlines the essential aspects of conducting a systematic review of an educational topic beginning with the work needed once an initial idea for a review topic has been suggested through to the stage when all data from the selected primary studies has been coded. It draws extensively on the wisdom and experience of those who have undertaken systematic reviews of professional education, including Best Evidence Medical Education systematic reviews. Material from completed reviews is used to illustrate the practical application of the review processes discussed. The paper provides practical help to new review groups and contributes to the debate about ways of obtaining evidence (and what sort of evidence) to inform policy and practice in education.